2022
DOI: 10.3390/ani12131688
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomography-Guided Fine Needle Biopsies of Vertebral and Paravertebral Lesions in Small Animals

Abstract: Fine needle biopsy (FNB) is an effective, minimally invasive and inexpensive diagnostic technique. Under computed tomography (CT)-guidance, lesions that have a difficult approach can be sampled to reach a diagnosis. The aim of this study is to describe the use of CT-guidance to obtain FNB from vertebral and paravertebral lesions in small animals. Ten dogs and one ferret that had undergone CT-guided FNB of vertebral and paravertebral lesions and had a cytological or a histological diagnosis were included in thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Although an open surgical approach provides a superior visual field of the affected disc and facilitates collection of a sizeable sample for culture and biopsy, associated risks include those associated with prolonged general anesthesia, hemorrhage, vertebral destabilization, and postoperative neurological worsening. Potential complications of percutaneous sampling of the intervertebral disc include inadvertent damage to the spinal cord, spinal nerves, or large vessels, worsening pain, progression of neurological deficits, and seeding of bacteria from the disc into the epidural space, subarachnoid space or both, however, these complications are reported to be rare in the currently available literature 19,20 . One aim of our study was to determine whether geographical differences existed with regard to infectious disease positivity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although an open surgical approach provides a superior visual field of the affected disc and facilitates collection of a sizeable sample for culture and biopsy, associated risks include those associated with prolonged general anesthesia, hemorrhage, vertebral destabilization, and postoperative neurological worsening. Potential complications of percutaneous sampling of the intervertebral disc include inadvertent damage to the spinal cord, spinal nerves, or large vessels, worsening pain, progression of neurological deficits, and seeding of bacteria from the disc into the epidural space, subarachnoid space or both, however, these complications are reported to be rare in the currently available literature 19,20 . One aim of our study was to determine whether geographical differences existed with regard to infectious disease positivity.…”
Section: Discussionmentioning
confidence: 99%
“…18 Intervertebral disc cultures were performed in 63 of 386 ( 16 space or both, however, these complications are reported to be rare in the currently available literature. 19,20 One aim of our study was to determine whether geographical differences existed with regard to infectious disease positivity. Our study found no significant differences in culture results between institutions, although this could have been affected by sample sizes that could be too low to allow for some comparisons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The T2W intensity in our case, suggested a melanin-containing lesion, which was considered more likely as it usually appears hypointense on these sequences ( 16 ). Despite the accuracy that may be achieved via evaluating all imaging sequences and diagnostic methods, histopathology remains the gold standard technique ( 17 , 18 ). In this case report, the histopathological analysis and the positive result for Melan-A immunohistochemistry confirmed the presence of a melanocytic neoplasm.…”
Section: Discussionmentioning
confidence: 99%